Identifying the drivers of patients' reliance on short-acting β2-agonists in asthma. (3rd August 2021) - Blakeston, Sarah; Harper, Gavin; Zabala Mancebo, Julen
Abstract: Background: One of the most commonly observed asthma treatment patterns is the underuse of inhaled corticosteroid (ICS) maintenance therapy when patients are not experiencing symptoms, and the predominant use of short-acting β2-agonists (SABAs) when patients are experiencing symptoms. This multinational study investigated the current beliefs and behaviors related to reliance on reliever inhalers among asthma patients, and the reasons why patients may not adhere to their recommended maintenance controller treatment. Methods: This was a qualitative research study, in which 80 patients with asthma who were receiving reliever therapy (i.e. SABAs) were interviewed, in-depth, for 60 min. The interview questions focused on the patients' experience of living with asthma and their inhaled treatment regimens. Results: The key insights identified in the interviews were (a) patients had a strong emotional attachment to SABA relievers driven by their efficacy and success in quickly alleviating asthma symptoms, with the reliever also becoming an emotional support; (b) patients typically did not understand that the frequent use of SABAs indicates poor asthma control; (c) patients had a misperception of ICS, which could lead to a delay in escalation and poor adherence; and (d) severe exacerbations improve adherence to ICS, but only temporarily in many cases. Conclusion: This study confirmed the poor level of control patients have over their asthma, and how this affects their lifestyle and daily activities. Our results also confirmed that the patients' perception of both the disease and treatment plays a key role in SABA reliance and ICS underuse.